Mediación didáctica de la tradición oral para el fortalecimiento de habilidades socioemocionales (2024)
The objective of this research is to design a pedagogical proposal mediated by the Oral Tradition that contributes to the strengthening of Socioemotional Skills in Transition and 6th grade students of the Octavio Paz and Las Gardenias Educational Institutions in Barranquilla, Colombia. It is based on the Rationalist Deductive approach, with a Rationalist-Critical Mixed paradigm. The treatment of this research is carried out through two stages of design, documentary and field. The documentary design considers the Institutional Educational Project (PEI), the Curriculum Frameworks, and the class planners, treated through the Content Analysis Technique. The field design is carried out with samples of 68 Transition students of the Octavio Paz Educational Institution, their parents and 3 teachers, and 109 6th grade students, their parents and 5 teachers of the Las Gardenias Institution, to whom the sample survey and interview techniques are applied. The findings indicate a good level of appropriation of the Oral Tradition of the socio-cultural context among students, parents and teachers, but also indicate the need to strengthen the socioemotional culture of the Institutions from the components provided by the strategic direction of the PEI to the areas of academic and community management. It is concluded that it is necessary to strengthen the socioemotional component of educational institutions, advancing in the development of a socioemotional curriculum, and in the establishment, implementation and monitoring of strategies for the socioemotional development of the educational community, a purpose in which the cultural heritage of the oral tradition of the socio-cultural context is valuable